ChemInform Abstract: Synthesis, Biochemistry, and Computational Studies of Brominated Thienyl Chalcones: A New Class of Reversible MAO‐B Inhibitors. Issue 42 (September 2016) - Mathew, Bijo; Haridas, Abitha; Ucar, Guelberk; Baysal, Ipek; Joy, Monu; Mathew, Githa E.; Lakshmanan, Baskar; Jayaprakash, Venkatesan
Abstract: The title chalcones are prepared and tested for their inhibitory activities towards human monoamine oxidase (hMAO).